Peramalan Operasional Reservasi dengan Program Minitab menggunakan Pendekatan Arima PT Surindo Andalan - Hadijah Hadijah (Bina Nusantara University, 2013)
PT. Surindo Andalan is a GSA (General Sales Agent) of the airline owned by Oman government, Oman Air. This study aims to analyze the forecasting of one period ahead (December 2012) flight reservation from Jakarta to Muscat (capital of Oman) using ARIMA approaches. In this analysis, the authors use MINITAB software for data processing. Starting with autocorrelation testing, it shows that data is stationer therefore differencing should be 0. There are 35 times during data proceed within ARIMA models which are available in MINITAB program. Based on the analysis result that the forecasting model ARIMA (2,0,4) has the smallest value of MS (2709.7) and MSE (225.808333), thus resulting December 2012 forecast amounted reach 122.609.